ANALISIS STRUKTURAL TIPOLOGI TAKUT DALAM AL-QUR'AN (PERSPEKTIF LINGUISTIK DAN SEMANTIK) - Rokim, Syaeful; Maya, Rahendra (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Fear is a characteristic inherent to humans in this world. However, if not well managed, it can lead to anxiety and distress. The Qur'an provides guidance for humans to regulate this fear so that it can be beneficial in life. This research employs a qualitative approach and descriptive analytical method. The explanation steps utilize maudhui interpretation, which involves collecting verses related to the theme, understanding the reasons for the revelation of the discussed verses, comprehending the meaning of words, and establishing connections between words with interrelated meanings in interpretation. The result of this thematic discussion is that the word